Effect of low-dose aspirin intervention on pre-eclampsia prevention in high-risk pregnant women and its impact on postpartum hemorrhage - Zhang, Fangfang; Wang, Huijuan (Frontiers in Medicine, 2024)
Background: Pre-eclampsia, characterized by hypertension and organ dysfunction during pregnancy, poses significant risks to both maternal and fetal health. Aspirin, known for its antiplatelet properties, has been extensively utilized to mitigate pregnancy-related complications.However, the efficacy of low-dose aspirin in managing pre-eclampsia among high-risk pregnant women and its potential impact on postpartum hemorrhage remain contentious topics.A retrospective analysis was conducted on 344 pregnant women diagnosed with high-risk factors for pre-eclampsia. Among them, 152 received intervention with low-dose aspirin, while the rest did not receive it. The incidence of pre-eclampsia, as well as related complications and outcomes associated with bleeding, were compared and evaluated between the two groups.The study findings indicate a significant reduction in the incidence of pre-eclampsia among pregnant women receiving low-dose aspirin intervention, along with a significantly reduced risk of complications. Additionally, there was no significant statistical difference in postpartum hemorrhage between the two groups (P > 0.05). The safety profile of aspirin usage was found to be favorable.Low-dose aspirin demonstrates promising efficacy as an intervention strategy for high-risk preeclamptic women. It does not increase the risk of postpartum hemorrhage and reduces the occurrence of complications associated with preeclampsia. Therefore, low-dose aspirin presents a potential preventive measure against adverse outcomes associated with high-risk pregnancies related to preeclampsia. Further research is necessary to validate and elucidate the optimal dosage and timing of administration for maximal benefits.